Short communication. performance of pneumatic spraying with an over-the-row sprayer in high density apple tree orchards - Gil Sierra, J.=700 1 Ortiz Cañavate, J.; Riquelme Sanhueza, J.
(Es, En)
ilus., 11 ref.
Keywords: MALUS SYLVESTRIS; RIEGO; METODOS DE RIEGO; PULVERIZACION; ESPAÑA; DISTRIBUCION DE GOTAS; PULVERIZACION ASISTIDA POR AIRE